Financial Monitoring in the Audit Firm: Assessing the Client’s Risk Profile - Lubenchenko, О. Е.; Shulha, S. V. (Statistics of Ukraine, 2024)
The article is devoted to important issues of performing the primary financial monitoring by audit firms as specially designated entities of the primary financial monitoring. In the article’s spotlight are the requirements of the Law of Ukraine “Preventing and Counteracting Legalization (Laundering) of Incomes Obtained by a Criminal Way, Financing of Terrorism and Financing of Dissemination of Weapons of Mass Destruction” as the framework for elaborating internal provisions, rules and documents on financial monitoring issues. The injunctions contained in the Decree of the Ukrainian Ministry of Finance No. 465 “Approval of the Criteria of Risks of Legalization (Laundering) of Incomes Obtained by a Criminal Way, Financing of Terrorism and Financing of Dissemination of Weapons of Mass Destruction” are also analyzed. The authors address main criteria and procedures of risk assessment, used in identifying and minimizing the risks of legalization of the incomes obtained by illicit ways, financing of terrorism and other illegal transactions. An algorithm for assessing the client’s risk profile was constructed, with a questionnaire for the audit firm’s client designed to determine its risk profile and including assessment of the client’s category and geographic location, service (product) type, way (channel) of service delivery to the client or service receipt by the client. An interview is conducted with the involvement of a client’s representative, with the results assessed by the audit firm management in scores. Eventually, the maximal general indicator is selected as the reference point for determining the level of risk of laundering the incomes obtained by illicit ways: unacceptably high; high; medium; low. The questionnaire needs to be compiled before business relations are set, i.e. at the phase of client acceptance and audit engagement. For better convenience, the criteria underlying the assessment of the client’s risk profile were aggregated in view of the operational specifics in audit firms, which is supposed to enhance the risk management efficiency. The proposed method for assessing the risk profile of an audit firm client assures the compliance with the legal requirements pertaining to the financial monitoring and equips audit firms with a tool to counteract laundering of money obtained by a criminal way, financing of terrorism and financing of dissemination of mass destruction weapons.